Bagaimana Komitmen Organisasional Memediasi Pengaruh Karakteristik Pekerjaan dan Employee Engagement terhadap Kinerja - Fanny Monica H Bedagama; Endang Tjahjaningsih (Telaah Bisnis, 2021)
This study aims to analyze the effect of job characteristics and employee engagement on performance by mediating organizational commitment to employees of PT Jati Luhur Agung Semarang. The research sample was all 115 employees of PT Jati Luhur Agung Semarang (Factory 1) with census sampling technique. The data analysis technique used instrument test, model test, regression test, and sobel test using SPSS 24 software. The results showed that job characteristics had no effect on organizational commitment. Employee engagement had a positive effect on organizational commitment. Job characteristics had a positive effect on performance. Employee engagement had a positive effect on performance. Organizational commitment had a positive effect on performance. Organizational commitment does not mediate the effect of job characteristics on performance while organizational commitment mediates employee engagement on performance.